In vitro mycorrhization of edible Astraeus mushrooms and their morphological characterization - Wanwisa Fangfuk (2018)
Astraeus is the most popular and the most expensive edible ectomycorrhizal mushroom group consumed in Thailand, although it is not commonly consumed in other countries. The purpose of this work was to test the ability of Astraeus to form ectomycorrhizae with seedlings of Pinus densiflora in vitro. A single 1-week-old P. densiflora seedling was transplanted into a glass bottle containing autoclaved forest soil, and suspensions of more than 106basidiospores of Astraeus odoratus or Astraeus hygrometricus were inoculated onto the seedling. Cultured mycelium was also inoculated onto an axenic pine seedling planted on sterilized vermiculite-sphagnum moss mixture in a glass bottle. Mycorrhization of A. hygrometricus was observed a few months after inoculation in both treatments. Fungal species identity of both the inoculum and ectomycorrhizae was assessed by PCR-RFLP analysis of the ITS region of rDNA. At 5-6 months after inoculation, A. hygrometricus ectomycorrhizae developed a sheath, rhizomorphs, and Hartig net on pine lateral roots. No ectomycorrhizal formation was found after A. odoratus inoculation. These results suggest that A. hygrometricus can form mycorrhizae on pine seedlings. The external morphological characteristics of A. hygrometricus ectomycorrhizae were distinct from those of other Boletales ectomycorrhizae. This article provides the first morphological and anatomical description of A. hygrometricus ectomycorrhizae. © 2010 The Mycological Society of Japan and Springer.